Self-monitoring for recurrence of secondary atrial fibrillation following non-cardiac surgery or acute illness: A pilot study - Nicole Lowres (International Journal of Cardiology: Heart & Vasculature, 2020)
Background: Atrial fibrillation (AF) secondary to non-cardiac surgery and medical illness is common and, although often transient, is associated with an increased risk of stroke and mortality. This pilot study tested the feasibility of self-monitoring to detect recurrent AF in this setting and the frequency with which it occurred. Methods: Patients with new secondary AF after non-cardiac surgery or medical illness that reverted to sinus rhythm before discharge were recruited in three tertiary hospitals in Australia. Participants performed self-monitoring for AF recurrence using a Handheld single-lead ECG device 3–4 times/day for 4-weeks. Results: From 16,454 admissions, 224 (1.4%) secondary AF cases were identified. Of these, 94 were eligible, and 29 agreed to participate in self-monitoring (66% male; median age 67 years). Self-monitoring was feasible and acceptable to participants in this setting. Self-monitoring identified AF recurrence in 10 participants (34%; 95% CI, 18% −54%), with recurrence occurring ≤ 9 days following discharge in 9/10 participants. Only 4 participants (40%) reported associated palpitations with recurrence. Six participants (60%) with recurrence had a CHA2DS2-VA score ≥ 2, suggesting a potential indication for oral anticoagulation. Conclusions: Approximately 1 in 3 patients with transient secondary AF will have recurrent AF within nine days of discharge. These recurrent episodes are often asymptomatic but can be detected promptly using patient self-monitoring, which was feasible and acceptable. Future research is warranted to further investigate the incidence of secondary AF, the rate of recurrence after discharge and its prognosis, and whether use of oral anticoagulation can reduce stroke in this setting.